2022
DOI: 10.7759/cureus.20954
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Impact of SARS-CoV-2 on a Level 1 Trauma Center Including Subgroup Analysis of Orthopedic Injuries and Mechanism of Injury

Abstract: Background and objectiveThere is a paucity of medical literature describing the preparedness of hospital institutions to withstand the population effects of a pandemic. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease 2019 (COVID-19), has had a global impact on all facets of medicine, which has ultimately affected the medical community in a significant manner. Furthermore, there is a scarcity of research regarding the effects of COVID-19 on trauma and acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We did not evaluate the detailed causes of these injuries in our patients, but there are reports that traffic restrictions resulted in a reduction in fractures associated with traffic accidents [ 48 ]. However, due to reduced public transport, children and young people were likely to use bicycles more often, so bicycle injuries were significantly higher during the pandemic [ 57 – 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…We did not evaluate the detailed causes of these injuries in our patients, but there are reports that traffic restrictions resulted in a reduction in fractures associated with traffic accidents [ 48 ]. However, due to reduced public transport, children and young people were likely to use bicycles more often, so bicycle injuries were significantly higher during the pandemic [ 57 – 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several efforts have been made to assess the impacts of COVID-19 on general injury trends globally, with countries reporting both increases and decreases in injuries. For example, studies found significant increases in trauma patient admissions from May to June of 2020 in Italy and from March 2020 to February 2021 in the United States ( Giudici et al, 2021 , Moore et al, 2022 ) and significant increases in unintentional injury deaths from March to August 2020 in the United States ( Faust et al, 2021 ). However, other studies found the number of injuries seen in some trauma centers significantly decreased while local COVID-19 stay-at-home orders were in place in the United States and England ( Sherman et al, 2021 , Sephton et al, 2021 ) and all-cause injury mortality significantly declined during the COVID-19 pandemic in Guangdong, China ( Zheng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%